Ablation of the cellular prion protein, PrPC, specifically on follicular dendritic cells has no effect on their maturation or function. Issue 3 (5th February 2013) - McCulloch, Laura; Brown, Karen L.; Mabbott, Neil A.
Summary Follicular dendritic cells (FDC) are situated in the primary follicles of lymphoid tissues where they maintain the structural integrity of the B‐lymphocyte follicle, and help to drive immunoglobulin class‐switch recombination, somatic hypermutation and affinity maturation during the germinal centre response. FDC can also provide a reservoir for pathogens that infect germinal centres including HIV and prions. FDC express high levels of the normal cellular form of the prion protein (PrPC), which makes them susceptible to prion infection. The function of PrPC is uncertain and it is not known why FDC require such high levels of expression of a protein that is found mainly on cells of the central nervous system. In this study, the function of FDC was assessed in mice that had PrPC ablated specifically in their FDC. In mice with FDC‐specific PrPC ablation, our analysis revealed no observable deficits in lymphoid follicle microarchitecture and FDC status. No effects on FDC ability to trap immune complexes or drive antigen‐specific antibody responses and affinity maturation in B lymphocytes were observed. These data clearly demonstrate that PrPC expression is dispensable for the functional maturation of FDC and their ability to maintain antigen‐specific antibody responses and affinity maturation.